THE MODEL STATUS OF THE HEAD OF THE SUBJECT OF THE RUSSIAN FEDERATION - V. V. Naumkina, (Scientific Journal of Pedagogy and Economics, 2020)
The relevance of the topic is determined that the highest official of the subject of the Russian Federation are central in the system of regional public authorities and has a significant impact on the performance of Federal state functions. The Federal structure of the Russian Federation provides for different levels of governance. The effectiveness of solving state problems depends on the quality of management in the regions. The legislation defines only the basic principles of the requirement of the organization of power in the subject of the Russian Federation. Subject of the Russian Federation can regulate the organization of management. Federal legislation provides the subjects of the Russian Federation with relative freedom in determining the system, structure, order of formation and functioning of the Executive power. The subjects of the Russian Federation are different models of governance, which determine the status of the head of the subject of the Russian Federation. The article identifies two models for realizing the principle of separation of powers in the subjects of the Russian Federation. The place of the head of the subject of the Russian Federation in the power system is considered from the position of the scope of powers. The article describes the status of the head of the subject of the Russian Federation when using different models, highlights the features of organizational models. The practical application of the management model depends on the characteristics of the territory (area, population, socio-economic situation). In contrast to the Federal model, the head of a subject of the Russian Federation in fact included in the system of Executive power regardless of the model. The article deals with discussion issues. The article highlights the main disadvantages and offers suggestions on the advantages of models.